Metastatic prostate cancer-associated P62 inhibits autophagy flux and promotes epithelial to mesenchymal transition by sustaining the level of HDAC6 - Jiang, Xianhan (Prostate, 2018)
P62 (also named sequestosome-1, SQSTM1) is involved in autophagy regulation through multiple pathways. It interacts with autophagosomes-associated LC3-II and ubiquitinated protein aggregates to engulf the aggregates in autophagosomes, interacts with HDAC6 to inhibit its deacetylase activity to maintain the levels of acetylated α-tubulin and stabilities of microtubules to enhance autophagosome trafficking, and regulates autophagy initiation and cell survival. We performed immunohistochemistry staining of P62 in prostate tissues from prostate cancer patients and found that levels of P62 in patients with prostate adenocarcinomas (PCA) are significantly higher than those in patients with benign prostate hyperplasia (BPH). High levels of P62 predict high tumor grade and high intensity of metastasis. Here we show that P62 increased the levels of HDAC6 and reduced the acetylation of α-tubulin and the stability of microtubules. Consequently, high levels of P62 caused a promotion of epithelial to mesenchymal transition in addition to an impairment of autophagy flux, and further led to an enhancement of proliferation, migration and invasion of prostate cancer cells. Therefore, P62 promotes metastasis of PCA.